Weight-bearing, muscle loading and bone mineral accrual in pubertal girls—A 2-year longitudinal study - Wang, Qingju; Alén, Markku; Nicholson, Patrick; Suominen, Harri; Koistinen, Arvo; Kröger, Heikki; Cheng, Sulin (Bone (New York, N.Y.), 2007)
Objectives: The mechanical environment is considered to be the most important determinant of bone strength. Local muscle force, in turn, is regarded as the largest source of loading applied to bones. However, the effect of weight-bearing on bone mineral accrual is unclear. Comparing the relationship between muscle force and bone mineral content (BMC) in the upper and lower limbs provides a means of investigating this issue. Subjects and methods: The study group comprised 258 healthy girls aged 10–13 years old at baseline. BMC, lean body mass (LM) and fat body mass (FM) of total body were assessed by dual-energy X-ray absorptiometry at baseline and 2 years after. The maximal isometric voluntary contraction (MVC) of left elbow flexors and knee extensors was evaluated by a dynamometer. A hierarchical linear statistical model with random effects was used to analyze the relationship between BMC and limb-matched MVC. Fisher's z-transformation was used to compare the correlation coefficients between arms and legs. The ratio of BMC to MVC (BMC/MVC) in upper and lower limbs was compared using Student's t-test. Results: BMC was highly correlated with MVC in arms and legs ( r 2 = 0.54 and 0.50, respectively), and the correlation coefficients did not differ between upper and lower limbs. On the other hand, BMC/MVC was significantly (30%) higher in leg than in arm. Conclusions: The results indicate that local muscle contraction and weight-bearing exert an additive effect on bone mass accretion in the lower limbs. Exercise regimes combining resistance and impact training should provide larger bone response than either one of them alone in growing children.